Komunikasi Pembangunan Program Pasar Tertib Ukur di Pasar Tradisional Johar Karawang - Hamzah, Khalid; Ramdhani, Muhammad; Nurkinan, Nurkinan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The presence of modern markets has had an impact on decreasing the turnover of traditional market traders in Karawang Regency. The government responded to this problem by creating a program called Pasar Tertib Ukur to improve the image of traditional markets and increase public visits to shop at traditional markets. One of the implementations of this program occurred at the Johar Karawang Market in 2017.This research aims to find out how communication occurs in the Pasar Tertib Ukur Program at Johar Karawang Market. Then, this research also finds out what changes occurred after the implementation of the Orderly Market Program in that market. Qualitative methods using data collection techniques with interviews, observation and documentation have been carried out in this research. Researchers linked the findings using the Diffusion and Innovation theory and the economic growth development model theory. The research results show that the development communication that occurs lies in the content of the program. The program focuses on guaranteeing measuring and weighing equipment at the Johar Karawang Market and consumer protection. The change that occurred after the program was implemented was an increase in the number of buyers at Johar Karawang Market. The conclusion of this research shows that the Orderly Measurement Market Program has succeeded in bringing about a change in the Johar Karawang Market and increasing its existence so that it is no less competitive with modern markets.